Glial cells as a promising therapeutic target of glaucoma: beyond the IOP - Shinozaki, Youichi; Namekata, Kazuhiko; Guo, Xiaoli; Harada, Takayuki (Frontiers in Ophthalmology, 2024)
Glial cells, a type of non-neuronal cell found in the central nervous system (CNS), play a critical role in maintaining homeostasis and regulating CNS functions. Recent advancements in technology have paved the way for new therapeutic strategies in the fight against glaucoma. While intraocular pressure (IOP) is the most well-known modifiable risk factor, a significant number of glaucoma patients have normal IOP levels. Because glaucoma is a complex, multifactorial disease influenced by various factors that contribute to its onset and progression, it is imperative that we consider factors beyond IOP to effectively prevent or slow down the disease’s advancement. In the realm of CNS neurodegenerative diseases, glial cells have emerged as key players due to their pivotal roles in initiating and hastening disease progression. The inhibition of dysregulated glial function holds the potential to protect neurons and restore brain function. Consequently, glial cells represent an enticing therapeutic candidate for glaucoma, even though the majority of glaucoma research has historically concentrated solely on retinal ganglion cells (RGCs). In addition to the neuroprotection of RGCs, the proper regulation of glial cell function can also facilitate structural and functional recovery in the retina. In this review, we offer an overview of recent advancements in understanding the non-cell-autonomous mechanisms underlying the pathogenesis of glaucoma. Furthermore, state-of-the-art technologies have opened up possibilities for regenerating the optic nerve, which was previously believed to be incapable of regeneration. We will also delve into the potential roles of glial cells in the regeneration of the optic nerve and the restoration of visual function.